Hesperidin alleviates zinc oxide nanoparticle induced hepatotoxicity and oxidative stress - Sabah Ansar; Manal Abudawood; Amal S. A. Alaraj; Sherifa S. Hamed (BMC, 2018)
Abstract Background Nanoparticles are widely utilized in many products such as cosmetics and sunscreens. The present study was undertaken to evaluate the effect of hesperidin (HSP) on nano zinc oxide particles (nZnO) induced oxidative stress in rat livers. Methods Rats were randomly divided into 4 groups of 6 rats each and exposed to single administration of nZnO intraperitoneally (600 mg/kg bwt) and HSP (100 mg/kg bwt) by gavage. Group I served as the control; group II was given nZnO only; groups III received HSP only and group IV received nZnO 1 h after pretreatment with HSP for 7 days. Results Compared to the controls, nZnO administration enhanced alanine aminotransferase (AST) and aspartate aminotransferase (ALT) levels (p < 0.05) with reduction in the levels of glutathione (GSH), catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD) and increase in levels of malondialdehyde (MDA) while HSP attenuated nZnO-induced hepatotoxicity for above mentioned parameters. Conclusions The induced toxicity in the liver was corrected by pretreatment with HSP. The findings of this study suggest that HSP pretreatment can potentially be used to prevent nZnO-induced biochemical alterations toxicity. Further, protection by HSP on biochemical results was confirmed by histopathological changes. The present study suggests that HSP can protect against nZnO-induced oxidative damage in the rat livers.